PENJATUHAN SANSKI PIDANA BAGI PELAKU PENYEBAR VIDEO PORNOGRAFI DI MEDIA SOSIAL DI PENGADILAN NEGERI KELAS IA KOTA LUBUKLINGGAU - Rezika, Nadila; Fransisco, Wawan; Fuadi, Ahmad (Law Journal (LAJOUR), 2025)
Pornography (Cyberporn) is usually done online via the internet, is a form of cybercrime that should be watched out for by the Indonesian people. Pornography is indeed a very complex thing that cannot stand alone, but rather a collection of several issues about pornography, not only a problem of the government and the state, but also concerns the lives of the community. This study uses normative-empirical (applied) research, this study examines the implementation or implementation of positive legal provisions (legislation) and written documents in action (factual) in every particular legal event that occurs in society. Pornography is an unlawful act and is prohibited by religion. Pornography does not maintain the honor of the perpetrator, family or society and is an act that defames, tarnishes, leads oneself or others astray, this has negative impacts such as free sex, sexual harassment, deviant sexual behavior, and so on. It is hoped that all law enforcement officers will more often conduct socialization to the community regarding the consequences of the crime of Making Pornographic Recordings or other Pornography crime.